Synergistic Effects of Extra X Chromosome on Development of Systemic Lupus Erythematosus and Sjögren Disease in Klinefelter and Triple X Syndrome: A Retrospective Cohort Study - Anna‐Kay Palmer; Irene J. Tan (ACR Open Rheumatology)
Objective Systemic lupus erythematosus (SLE) and Sjögren disease (SjD) are autoimmune diseases with significant female predominance. The prevalence of SLE is increased in Klinefelter syndrome (KS) compared with the general male population. Our study investigates the dose effects of extra X chromosomes on the development of SLE and SjD in KS and triple X syndrome compared with the general population. Methods This multicenter, retrospective cohort study used TriNetX, a global federated research database. Using International Statistical Classification of Diseases, Tenth Revision, Clinical Modification codes, patients with a diagnosis of SLE or SjD in the general population, as well as those with SLE and SjD in KS (karyotype 47,XXY) and triple X syndrome (karyotype 47,XXX) from January 1, 2010, to January 1, 2024, were identified. Fisher's exact test was used to calculate the relative risk of SLE and SjD in males with KS and females with triple X syndrome compared with the general population. The 95% confidence intervals (95% CI) were obtained with STATA statistical software. Results A total of 113,748,373 patients were identified. The prevalence of SLE and SjD was 0.59% and 0.077%, respectively, in men, and 0.381% and 0.388% for SLE and SjD, respectively, in women. The male‐to‐female ratios for all ages were 1:6.4 for SLE and 1:5 for SjD. The prevalence of KS and triple X syndrome in the general population was 0.0017% and 0.0010%, respectively. Among patients with KS, the prevalence of SLE and SjD was both 0.5%. Among patients with triple X syndrome, the prevalence of SLE and SjD was 1.3% and 0.8%, respectively. SLE was 8.5‐fold (95% CI 4.6–15.8) and SjD was 6.6‐fold (95% CI 3.56–12.26) more common in KS compared with the general male population (P < 0.001 by Fisher's exact test). SLE was 3.5‐fold (95% CI 2.09–5.72) and SjD was 2.3‐fold (95% CI 1.22–4.20) more common in triple X syndrome compared with the general female population (P < 0.001 and P < 0.05, respectively). Conclusion The extra X chromosome in KS and triple X syndrome appears to confer a nonproportional, synergistic dose effect on the development of SLE and SjD when compared with the general population.